High-throughput protein nanopatterning. (1st August 2019) - Liu, Xiangyu; Kumar, Mohit; Calo', Annalisa; Albisetti, Edoardo; Zheng, Xiaouri; Manning, Kylie B.; Elacqua, Elisabeth; Weck, Marcus; Ulijn, Rein V.; Riedo, Elisa
Abstract : We demonstrate a high resolution and high-throughput patterning method to generate protein nanopatterns with sub-10 nm resolution by using thermochemical scanning probe lithography. Abstract : High-throughput and large-scale patterning of enzymes with sub-10 nm resolution, the size range of individual protein molecules, is crucial for propelling advancement in a variety of areas, from the development of chip-based biomolecular nano-devices to molecular-level studies of cell biology. Despite recent developments in bio-nanofabrication technology, combining 10 nm resolution with high-throughput and large-scale patterning of enzymes is still an open challenge. Here, we demonstrate a high resolution and high-throughput patterning method to generate enzyme nanopatterns with sub-10 nm resolution by using thermochemical scanning probe lithography (tc-SPL). First, tc-SPL is used to generate amine patterns on a methacrylate copolymer film. Thermolysin enzymes functionalized with sulfonate-containing fluorescent labels (Alexa-488) are then directly immobilized onto the amine patterns through electrostatic interaction. Enzyme patterns with sub-10 nm line width are obtained as evidenced by atomic force microscopy (AFM) and fluorescence microscopy. Moreover, we demonstrate large-scale and high throughput (0.13 × 0.1 mm 2 at a throughput of 5.2 × 10 4 μm 2 h −1 ) patterning of enzymes incorporating 10 nm detailed pattern features. This straightforward and high-throughput method of fabricating enzyme nanopatterns will have a significant impact on future bio-nanotechnology applications and molecular-level biological studies. By scaling up using parallel probes, tc-SPL is promising for implementation to scale up the fabrication of nano-biodevices.